THE SPECIFICITY OF STATE POLICY IN ENSURING ECONOMIC DEVELOPMENT OF RUSSIA - Marina Ribasova (Вестник Северо-Кавказского федерального университета, 2022)
In this article the author discusses the main problems faced by the Russian economy today. Studied economic problems, including falling oil prices, economic sanctions and the weakening of the domestic market. The article describes the problem of Western sanctions, economic embargo, the unstable geopolitical situation, falling oil prices, as well as many other factors that led the country into a state ofsevere recession. Russia's path to economic recovery and growth depend on the pace of reform, especially in the next two years. In the scientific article it is proved that the introduction of structural changes is especially important for Russia's aspirations at the same time to implement a demographic and economic transformation in the long term